VERBA PREDIKATIF BAHASA TOKOH WANITA DAN JURU CERITA NOVEL GENDUK - Abdul Ageng Firmansyah; Kahfie Nazaruddin; Munaris Munaris (FKIP Universitas Lampung, 2020)
The problem in this study is the use of predicative verbs in the language of female characters and storytellers contained in the novel Genduk by Sundari Mardjuki. The method used in this research is descriptive qualitative method and makes the novel Genduk by Sundari Mardjuki as a data source. Data analysis technique in research is text analysis. The results of the research show that the predicative verbs in the language of women characters and storytellers contained in the novel Genduk by Sundari Mardjuki are using intransitive verbs, monotransitive verbs, and ditransitive verbs. The use of predictive verbs in Sundanese novel Mendjuki's Genduk can be used as an alternative teaching material in high school. Masalah dalam penelitian ini adalah penggunaan verba predikatif bahasa tokoh wanita dan juru cerita yang terdapat dalam novel Genduk karya Sundari Mardjuki. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dan menjadikan novel Genduk karya Sundari Mardjuki sebagai sumber data. Teknik analisisis data dalam penilitian adalah analisis teks. Hasil penelitian menunjukan verba predikatif bahasa tokoh wanita dan juru cerita yang terdapat dalam novel Genduk karya Sundari Mardjuki adalah menggunakan verba taktransitif, verba ekatransitif, dan verba dwitransitif. Penggunaan verba predikatif dalam novel Genduk karya Sundari Mardjuki dapat digunakan sebagai alternatif bahan ajar di SMA.Keywords: predicative verbs, novels, teaching materials.